A meme for money - L. Randall Wray (Levy Economics Institute of Bard College, 2012)
This paper argues that the usual framing of discussions of money, monetary policy, and fiscal policy plays into the hands of conservatives.That framing is also largely consistent with the conventional view of the economy and of society more generally. To put it the way that economists usually do, money lubricates the market mechanism - a good thing, because the conventional view of the market itself is overwhelmingly positive. Acknowledging the work of George Lakoff, this paper takes the position that we need an alternative meme, one that provides a frame that is consistent with a progressive social view if we are to be more successful in policy debates. In most cases, the progressives adopt the conservative framing and so have no chance. The paper advances an alternative framing for money and shows how it can be used to reshape discussion. The paper shows that the Modern Money Theory approach is particularly useful as a starting point for framing that emphasizes use of the monetary system as a tool to accomplish the public purpose. It is not so much the accuracy of the conventional view of money that we need to question, but rather the framing. We need a new meme for money, one that would emphasize the social, not the individual. It would focus on the positive role played by the state, not only in the creation and evolution of money, but also in ensuring social control over money. It would explain how money helps to promote a positive relation between citizens and the state, simultaneously promoting shared values such as liberty, democracy, and responsibility. It would explain why social control over money can promote nurturing activities over the destructive impulses of our undertakers (Smith's evocative term for capitalists).
Keywords: A11; A12; A14; B15; B50; E21; E42; E44; E50; E62; H1; H40; H60; H62; H63; 330